2017
DOI: 10.15406/mojce.2017.03.00075
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Construction Project Performance Estimators

Abstract: This paper did a survey of literature on construction project performance. The industry's consensus on construction project performance estimators are well validated by these literatures as time, cost and quality. The findings showed that poorly performing construction projects are characterized by cost and time overruns as evident in high cost of construction, low quality work and time escalations. Research attempts in the industry to respond to these negative impacts on performance have yielded results in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…While the study showed [5] how to manage quality in construction projects in Syria this study concluded that the construction projects in Syria suffer from some imbalances and shortcomings the research presented some solutions and suggestions that could contribute to avoiding some quality management problems in this industry.…”
Section: Literature Reviewmentioning
confidence: 91%
See 4 more Smart Citations
“…While the study showed [5] how to manage quality in construction projects in Syria this study concluded that the construction projects in Syria suffer from some imbalances and shortcomings the research presented some solutions and suggestions that could contribute to avoiding some quality management problems in this industry.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Egwunatum [5], found in their studies, that the relationship between various independent variables and project success varies according to the project life cycle. [6], found in his research, that CSFs do not give real life knowledge of a project's success.…”
Section: A Project Performancementioning
confidence: 99%
See 3 more Smart Citations